Masks, mosques and lockdowns: Islamic organisations navigating the COVID-19 pandemic in Germany - Emmerich, Arndt (Entangled Religions, 2022)
The article investigates COVID-19 related responses by Islamic associations and local mosques based on fieldwork in the German state of Lower Saxony. The inquiry focuses on the time prior to the first lockdown, during mosque closures, and around the opening phase, covering the months between February 2020 and November 2020. Drawing on organisational sociology, Islamic studies, and research on pandemics, the article contributes to the debate on the contested nature of Islamic representation and the institutionalisation of Islam in Germany by analysing internal and relational dynamics, different and converging strategies, external challenges, and cooperation by Islamic authorities during the first COVID-19 wave. By taking into account Germany’s multilevel political system including the national, state, and municipal level as well as transnational dimensions, the analysis integrates external expectations on Islamic organisations and local mosques and internal discussions within these institutions to relate their responses and navigation to the contested representations of Islamic organisations in public discourse as well as to the current debate on Islam in Germany.